The Influence of Character Education on the Students' Academic Behavior in Islamic Education Subject at V Class a Public Elementary School - Herdianto Wahyu Pratomo; Ahmad; Sulaeman; Alvian (Educan : Jurnal Pendidikan Islam, 2023)
Teachers oblige to instill social values in students to improve the quality of character education. By doing so, it is expected that there will be changes in the character and personality of students. This study aims to scientifically analyze the influence of character education on students' academic behavior in Islamic education subjects among fifth-grade students of public elementary school Cikalong 1, Majalengka Regency. Researchers use descriptive and survey methods by plunging directly into the field and taking data at the time of the research to determine, study, and describe the influence between variables. Based on the survey results, the researchers expect that the implementation of character education will improve the students' academic behavior. However, symptoms still reflect the value of student academic behavior that does not align with the values of character education. The results showed a good influence of character education on student academic behavior, with a correlation of 0.587 and a coefficient of determination of 65.5%. Linkage factors are given in the medium category, and 34.5% of other factors are linked with the academic behavior of public elementary school students Cikalong 1, Majalengka Regency. This 34.5% of other factors include the influence of the family, the Influence of the community environment, and the Influence of innate or hereditary traits.